Novel Identified Receptors on Mast Cells - Migalovich-Sheikhet, Helena; Friedman, Sheli; Mankuta, David; Levi-Schaffer, Francesca (Frontiers in Immunology, 2012)
Mast cells (MC) are major participants in the allergic reaction. In addition they possess immunomodulatory roles in the innate and adaptive immune reactions. Their functions are modulated through a number of activating and inhibitory receptors expressed on their surface. This review deals with some of the most recently described receptors, their expression patterns, ligand(s), signal transduction mechanisms, possible cross-talk with other receptors and, last but not least, regulatory functions that the MC can perform based on their receptor expression in health or in disease. Where the receptor role on MC is still not clear, evidences from other hematopoietic cells expressing them is provided as a possible insight for their function on MC. Suggested strategies to modulate these receptors' activity for the purpose of therapeutic intervention are also discussed.